Kajian Interaksi Gajah Sumatera (Elephas Maximus Sumatranus) Dengan Masyarakat Kuyung Arang, Kabupaten Tanggamus - Dina Farida Utami; Agus Setiawan; Elly Lestari Rustiati (Department of Forestry, Faculty of Agriculture, University of Lampung, 2015)
Study on the interaction and its effects between sumateran elephants and Kuyung Arang's local people, Tanggamus was conducted in October-December 2014, direct and indirect observation, by questionnaire was applied. Amensalism is the interaction found between sumatran elephants and local people of Kuyung arang. Negative impacts include harvest fail (29.58%; n=21), crop (60.56%; n=43), and hut (9.86%; n=7) destruction. Keywords: Sumatran elephant, interaction, local people, Kuyung Arang, Bukit Barisan Selatan National Park